2009
DOI: 10.1186/1742-2094-6-16
|View full text |Cite
|
Sign up to set email alerts
|

Unique aspects of transcriptional regulation in neurons - nuances in NFkappaB and Sp1-related factors

Abstract: The unique physiology and function of neurons create differences in their cellular physiology, including their regulation of gene expression. We began several years ago exploring the relationships between the NFκB transcription factor, neuronal survival, and glutamate receptor activation in telencephalic neurons. These studies led us to conclude that this population of cells is nearly incapable of activating the NFκB that is nonetheless expressed at reasonable levels. A subset of the κB cis elements are instea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 96 publications
1
47
0
Order By: Relevance
“…We and others have previously shown that astrocytes display prominent NFκB activity (Herkenham et al, 2011; Lian et al, 2012; Mao et al, 2009). Consistent with an astrocytic bias in NFκB signaling, we found that IκBα, a known downstream target of NFκB, was expressed at substantially higher levels in astroglia than in neurons under both basal (~5-fold) and TNFα-stimulated conditions (~50-fold) (Figure S1B).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We and others have previously shown that astrocytes display prominent NFκB activity (Herkenham et al, 2011; Lian et al, 2012; Mao et al, 2009). Consistent with an astrocytic bias in NFκB signaling, we found that IκBα, a known downstream target of NFκB, was expressed at substantially higher levels in astroglia than in neurons under both basal (~5-fold) and TNFα-stimulated conditions (~50-fold) (Figure S1B).…”
Section: Resultsmentioning
confidence: 90%
“…These activities have been attributed, at least in part, to the presence of constitutive NFκB activity in neurons (Blondeau et al, 2001; Kaltschmidt et al, 2000; Kaltschmidt et al, 1993, 1995; Kaltschmidt et al, 1994). However, recent studies by us and others reported that, compared to astroglia, neurons exhibit negligible NFκB activity (Lian et al, 2012; Mao et al, 2009). Consistent with this assessment, we found that both IκBα and C3 are expressed at substantially higher levels in astroglia compared to neurons under both basal and TNFα-stimulated conditions.…”
Section: Discussionmentioning
confidence: 91%
“…Jang et al (35) further reported that the deletion of nuclear factor B (NF-B) signaling in POMC neurons prevented LPS-induced anorexia. However, it must be emphasized that the results of the latter study have been directly contradicted by a large body of literature demonstrating that NF-B signaling is largely unresponsive in neurons (67)(68)(69)(70). Additionally, the administration of peripheral LPS exclusively stimulated NF-B signaling in nonneuronal brain cells (71,72).…”
Section: Role Of the Arc In Inflammatory Anorexiamentioning
confidence: 83%
“…The insertion allele of rs71815143 is predicted to contain three Sp1 binding sites and a CCAAT/enhancer binding protein (C/EBP) binding site, which are not predicted for the deletion allele. Sp1 is a ubiquitous transcriptional activator, except in the CNS, where it is expressed exclusively in early forebrain neurons (Mao et al 2009). C/EBP recruits transcriptional activators to enhancer and promoter regions (Calella et al 2007).…”
Section: Resultsmentioning
confidence: 99%